2007
DOI: 10.1021/ie0610905
|View full text |Cite
|
Sign up to set email alerts
|

Solubility, Diffusivity, and Permeability of Gases in Phosphonium-Based Room Temperature Ionic Liquids:  Data and Correlations

Abstract: Reported are the solubility, diffusivity, and permeability data for various gases in five phosphonium-based ionic liquids at 30 °C, as determined with a lag-time technique. The ionic liquids have a viscosity range of 200-3000 cP. The gas solubilities and diffusivities of the phosphonium-based ionic liquids are of the same magnitude as the gas solubilities for the more familiar imidazolium-based liquids. The gas diffusivity appears to be inversely proportional to the viscosity with an average power of 0.35 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
211
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(235 citation statements)
references
References 12 publications
20
211
1
3
Order By: Relevance
“…Remarkably faster diffusion of solute molecule has also been reported for RTILs composed of phosphonium cations; 29,40,44 e.g., the diffusion coefficients of CO, DPA, and DPCP did not follow the viscosity dependence obtained for other RTILs, and were much faster than expected from the relation. 29 It has been suggested that the solute molecules may diffuse more rapidly by moving through the void space due to the much bulkier structure of this cation.…”
Section: Pressure Dependence Of the Diffusion Coefficientsmentioning
confidence: 76%
“…Remarkably faster diffusion of solute molecule has also been reported for RTILs composed of phosphonium cations; 29,40,44 e.g., the diffusion coefficients of CO, DPA, and DPCP did not follow the viscosity dependence obtained for other RTILs, and were much faster than expected from the relation. 29 It has been suggested that the solute molecules may diffuse more rapidly by moving through the void space due to the much bulkier structure of this cation.…”
Section: Pressure Dependence Of the Diffusion Coefficientsmentioning
confidence: 76%
“…Several works have reported an inversely proportional relationship between IL viscosity and gas diffusivity. 23,[45][46][47] For instance, Scovazzo and co-authors proposed a general correlation, 23 which has been used as follows:…”
Section: Synthesis Of Poly(ionic Liquidmentioning
confidence: 99%
“…17,18 Consequently, several studies on the permeation properties of gases through SILM systems have explored the effect of the IL structure. Relating to the influence of the cation, a number of groups have investigated the gas permeation properties of different families of ILs (imidazolium, [19][20][21][22][23][24][25][26][27][28][29][30] phosphonium, 31,32 sulphonium, 32 pyridinium, 33 and ammonium 34 ) and improved results were obtained for imidazolium-based SILMs in terms of permeability and selectivity. Other studies, also focused on imidazolium ILs, explored different structural variations of the cation in order to enhance CO 2 solubility and selectivity.…”
Section: Introductionmentioning
confidence: 99%